Ответ:
(х-4)2-64=0
х2-16-64=0
х2-80=0
х2=80
(x-4)²-64=0
x²-8x+16-64=0
x²-8x-48=0
D=(-8)²-4*1*(-48)= 256
x1,2= (-(-8)+-√256)/2= (8+-16)/2
x1=(8+16)/2=12
x2=(8-16)/2=-4
Ответ: -4; 12
Объяснение:
сначала воспользуемся формулой сокращённого умножения
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
(х-4)2-64=0
х2-16-64=0
х2-80=0
х2=80
Ответ:
(x-4)²-64=0
x²-8x+16-64=0
x²-8x-48=0
D=(-8)²-4*1*(-48)= 256
x1,2= (-(-8)+-√256)/2= (8+-16)/2
x1=(8+16)/2=12
x2=(8-16)/2=-4
Ответ: -4; 12
Объяснение:
сначала воспользуемся формулой сокращённого умножения